Exploring the Alignment of Professional Development and Classroom Practices in African Contexts: A Discursive Investigation - Oluwatoyin Ayodele Ajani (Journal of Integrated Elementary Education, 2023)
Professional development plays a pivotal role in ensuring high-quality education. Well-designed activities empower teachers and improve instructional delivery. Therefore, this study examines the alignment of teacher professional development with classroom practices to meet learner needs. The study conducted a systematic literature review using the PRISM approach, focusing on research from 2003 to 2023 in EBSCO, Google Scholar, and other repositories. Only open-sourced and peer-reviewed English literature was considered. The findings emphasize that teacher professional development aims to equip educators with contemporary knowledge, skills, values, and attitudes that enhance teaching and learning excellence. When structured effectively, these activities boost pedagogical prowess and improve academic outcomes. The study highlights the significance of tailored, learner-centered pedagogical approaches and ongoing professional development opportunities to enhance academic performance. To facilitate effective teacher professional development, the study introduces the Learner-Centered Teacher Professional Development Model (LCTPD). It recommends integrating quality-driven, suitable professional development activities to enhance teaching practices and advance learners' performance.